MEMBANGUN KESADARAN LINGKUNGAN BERSIH DI SDN 1 PLOSOGENENG JOMBANG - Irianto, Bambang S.; Pratama, Alfian Diko; Ardiano, Aditya Rafli; Budhi W., M. Arief; Azhari, Riga Nurizqi (UNIVERSITAS SERAMBI MEKKAH, 2024)
Developing a clean-environment consciousness is a community outreach initiative carried out by the MBKM Internship Student Team, Faculty of Law, UPN